Identification of Secondary Metabolites and FT-IR Analysis of Getih-Getihan Fruit Extract (Rivina humilis L.) - Mariyam; Yulistia Anggraini; Tati Suhartati (Universitas Andalas, 2023)
Getih-getihan (Rivina humilis L.) plants can be used as antibacterial, antioxidant and natural pesticides. Most of the biological activities of natural products originated from secondary metabolites contained therein. Studies have shown the effects of leaves, branches, and fruits extract of R. humilis towards biological activities. However, identifying the phytochemical compounds of R. humilis L. fruit is less discussed. Here we proposed research on the identification of secondary metabolite compounds of R. humilis L. fruit extract using phytochemical screening tests and spectroscopic method. The extraction of R. humilis L. fruit was proceeded by maceration method using methanol solvent. The series of phytochemical screening tests signified the presence of alkaloids, terpenoids, tannins and flavonoids. Furthermore, we applied FT-IR analysis to confirm the existence of functional groups in the secondary metabolite compounds. A broad absorption band showed the hydroxyl groups (O-H) at 3265 cm-1. The sharp band at 1632 cm-1 exhibited the C=C stretching band. The presence of C-N (stretching) was signified by the absorption band at 1237 cm-1, while the C-H bond in CH3 terminals (alkanes, alkyl group) was exhibited at 1401 cm-1. All the functional groups confirmed in the FT-IR analysis corroborated the phytochemical test results.